Knochenverlust nach bariatrischen Eingriffen - Messner, Z.; Kocijan, A.; Kocijan, R. (Osteologie, 2018)
Bariatrische Chirurgie stellt eine effektive Behandlungsmethode für pathologische Adipositas dar. Neben den positiven kardiovaskulären Effekten kommt es jedoch zu zahlreichen negativen Effekten auf den Knochenmetabolismus. Die Genese des Knochenverlustes ist multifaktoriell und inkludiert Malabsorption, Vitamin D-Insuffizienz, Hypokalzämie, Hyperparathyreoidismus, “skeletal unloading” und einen erhöhten Knochenturnover. Das Resultat ist ein Verlust von Knochendichte und -struktur, sowohl im trabekulären als auch im kortikalen Bereich. Zusätzlich kommt es zu einem Abfall der Muskelmasse. Veränderungen im Knochenstoffwechsel normalisieren sich innerhalb von 2 Jahren. Der Knochendichteverlust dürfte jedoch anhalten. Die aktuelle Datenlage gibt Evidenz über ein erhöhtes Frakturrisiko bereits 2 Jahre nach bariatrischem Eingriff. Langzeitstudien haben jedoch eine weitere Zunahme des Frakturrisikos über 10 Jahre und mehr gezeigt. Frakturen treten sowohl an Osteoporose-typischen, als auch Osteoporose-untypischen Stellen auf. Eine Vitamin D-, Kalzium- und Proteinsubstitution scheint bereits präoperativ unerlässlich, um dem postoperativen Knochenmasseverlust entgegen zu wirken.Obesity is an increasing global burden, associated with increased risk for co-morbidities and mortality. Bariatric procedures, such as Rouxen-γ gastric bypass (RYGB) and sleeve gastrectomy (SG) are effective treatment options to reduce body weight and cardiovascular risk. However, numerous negative effects on bone metabolism have been reported. Bone loss seems to be multifactorial, including malabsorption, vitamin D insufficiency, hypocalcemia, hyperparathyreoidism, “skeletal unloading” and an increased bone turnover. An intestinale inflammation and changes in the RANKL (Receptor activator of NF-kB Ligand)/Osteoprotegerin (OPG)-ratio could also be explanations for bone loss after bariatric surgery. Consequently, bone mineral density decreases and bone microstructural deteriorations occur in both, trabecular and cortical bone. Bone turnover seems to normalize after two years, however, bone loss continues. An increased fracture risk has been reported in many, but not all studies, mostly depending on type of procedure. An elevated risk for fractures was reported at year two after operation with a continuing incline over time. Fractures occur at typical (hip, radius) and atypical (fingers, toes, sternum) sides. Besides bone loss, RYGB and SG are also associated with muscle loss and sarcopenia. There is strong evidence for vitamin D, calcium and protein substitution to avoid bone and muscle loss as well as high bone turnover after bariatric surgery. The substitution should be started preoperatively.
Keywords: Bariatrische Chirurgie; Osteoporose; Vitamin D; Ernährung